Phytogenic additives: essential oils for broilers - review (Research, Society and Development, 2020)
Phytogenic additives have been shown to act as a substitute for antibiotics because of their functionality in breaking up bacterial membranes, being effective in combating microorganisms and acting as antioxidants. Used in a strategic way, in promoting action, it will mainly favor the intestinal condition, increasing the zootechnical gains and increasing the prevention of pathologies associated with bacteria or fungi. Therefore, the aim of this review was to seek scientific information on what are the phytogenic additives, their compositions and mode of action and the applicability with the results obtained through their use in broiler feed. For this review an analysis was made of scientific studies that studied which are the main additives and their active principles, as well as their mode of action of essential oils and which plants have potential to be used as phytogenic additives, evidencing their effects on food. of broiler chickens. It is concluded that the use of phytogenic actives in the form of essential oils can be used in chicken feed, providing improvements in the intestinal health of birds and consequently improvement in their productive performance. Even if its positive points are shown, some conditions still need to be elucidated, such as dose / action relationship and association of the various active principles belonging to the phytogenic additives, which may provide several new studies.